Soil compaction response to wheel traffic in the Rolling Pampas region of Argentina - Contessotto, Enrique Ernesto; Botta, Guido Fernando; Angelini, Marcos Esteban; Bienvenido, Fernando; Rivero, David; Pelizzari, Federico Matías; Ghelfi, Diego Gabriel; Nistal, Ayelén Ileana (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2022)
The present work shows the effects of the different agricultural wheels traffic on the physical properties of a typical Argiudol soil worked under a no-tillage cropping system. Soil compaction produced by traffic was quantified through a series of parameters. These parameters were: a) cone index, b) rut depth and c) soil water content at the traffic moment. A grain chaser, a sprayer, a combine harvester and a tractor equipped with commonly used wheels were tested in the study area. The main results obtained showed that the tyres with the highest inflation pressure and tyre ground pressures produced the highest values of cone index and rut depth. A typical Argiudol soilis not able to constrain topsoil and subsoil compaction when wheeled by tyres with ground pressures greater than 77.6 kPa. This occurs when this soil is worked under a continuous no-tillage cropping system.